Exploring trajectories of depressive symptoms in North Korean defectors: A latent class mixed analysis - Kim, Dahae; Park, Sohee; An, Ji Hyun; Kim, Myung Hyun; Chang, Hyein; Hong, Jin Pyo (Frontiers in Psychiatry, 2022)
Background: North Korean defectors (NKDs) are known to be vulnerable to depression due to the influence of various psychosocial factors during their settlement process. Therefore, this study aimed to explore different trajectories of depressive symptoms in NKDs and identify predictors of the worsening of depressive symptoms. In particular, the focus was on whether posttraumatic stress disorder (PTSD) functions as a significant predictor. Methods: Participants consisted of 300 NKDs who settled in South Korea within three years of entering in the country. Five waves of longitudinal data collected from 2016 to 2019 were used. In this study, the North Korean Composite International Diagnostic Interview (NK-CIDI), a diagnostic interview tool, was conducted at baseline and depressive symptoms were measured at each wave. Trajectory identification was based on latent class mixed modeling. Logistic regression was used to extract the significant factors predicting a high/increasing depressive symptom trajectory. Results: Two trajectories of depressive symptoms were identified: “low/stable symptom” (76.7% of participants) and “high/increasing symptom” (23.3% of participants). Predictors of the high/increasing symptom group were being female and a low use of mental health services. Generalized anxiety disorder, social phobia, and alcohol dependence acted as significant predictors. Although PTSD was not a significant predictor, self-reported PTSD symptom scores were high in the high/increasing symptom group. Conclusions: Identifying the trajectories of depressive symptoms in NKDs helps identify the risk factors of clinically vulnerable groups. In the process of establishing government-level interventions, it may be helpful to create a therapeutic environment. In addition, when evaluating initial psychiatric problems, it is important to primarily consider NKDs’ anxiety levels and alcohol problems. There should also be an appropriate consideration of PTSD symptoms.